Labour Participation in Different Firm Organisations - Michele Moretto; Gianpaolo Rossini (Fondazione Eni Enrico Mattei (FEEM), 1999)
The main issue is the organisation of firms when different degrees of labour participation are taken into account. We start reviewing the literature on the LM firm. We then consider a less radical labour participation, i.e. the Aoki firm. We survey extensions of the Aoki's firm to the case of market uncertainty, where also the question of the optimal allocation of the shut down decision is tackled, when shareholders are not able to maximise the total payoff accruing to both workers and owners. By and large, it appears that the degree of labour participation in decisions and rent sharing in a firm is not a settled question, even though is seems to depend on the respective degree of firm specificities of production factors.
Keywords: L20; D92; 330; Labour participation; Firm organisation; Theorie der Unternehmung; Unternehmensorganisation; Betriebswirtschaftliches Ziel; Selbstverwalteter Betrieb; Mitarbeiterkapitalbeteiligung; Risiko; Erfolgsbeteiligung; Theorie